Registered taxpayers and tax collection in Peru during the COVID-19 pandemic 2020-2021 - Astulla Suarez, Dhayana; Meneses De La Cruz, Milagros; Burgos Zavaleta, Fernando (mktDESCUBRE; Vol 1 No 20 (2022): Twentieth Edition (July - December), 2022)
The objective of this research is to determine if the variation in the number of taxpayers during the COVID-19 pandemic had a correlation with tax collection in Peru during the years 2020 - 2021. The research design was non-experimental. correlational descriptive, for this statistical information was compiled from SUNAT and CEPALSTAT, considering the population of active taxpayers. The multiple linear regression model was applied, data processing was carried out using the Eviews application and Microsoft Excel digital tools. The results obtained showed that the variation in the number of taxpayers during the COVID-19 pandemic did not have a significant relationship with tax collection in Peru, in the years 2020 and 2021, concluding that there was an increase in registered taxpayers, while that, tax collection decreased especially in 2020, due to economic events and restrictions, as well as non-compliance and informality gaps.